KOMPETENSI KOLABORASI DALAM PROYEK KARYA ECOPRINT TEKNIK FREMENTASI DAUN PADA PEMBELAJARAN SENI RUPA SISWA KELAS V SD N 3 EMPAT LAWANG - Kartika Widya Sari; Dwi Anggraini; Yuli Amaliyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the application of collaboration competence in an ecoprint project using the leaf fermentation technique in arts education for fifth-grade students at SD Negeri 3 Empat Lawang. The research uses a naturalistic qualitative approach with fifth-grade VB students as subjects. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. Data validity was ensured through triangulation and member checks. The results show that learning ecoprint with the leaf fermentation technique can develop students' collaboration competence, including the ability to work together effectively, build positive working relationships, appreciate members' contributions, show respect, participate actively, solve problems together, and create a harmonious working atmosphere. Group 2 showed the most optimal development in collaboration competence because all indicators consistently appeared.